2009
DOI: 10.1080/00387010802428666
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Study of Coumarins: Correlation Between Charges of Atoms and Fragmentation Processes

Abstract: The mass spectrometry of a number of 6-substituted coumarins was studied in the context of correlating fragmentation pathways and electronic charges of atoms performed by AM1 semiempirical method. The atomic charges of atoms are found to be good predictors of the fragmentation pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The cleavage of the lactone ring take place at O 1 and then looses the CO after breaking the C 2 -C 3 bond, to give fragment A as indicated in the Schemes 2 and 3. When X = OH or NH 2 , fragment A (M-28) is the most abundant fragment as previously observed [11][12]14] and can lead to many other fragments as illustrated in the Schemes 2 and 3: Whether X = OH or NH 2 , the same fragmentation processes were practically obtained and good correlation with the electronic charges of atoms were observed. In this case, most of important fragmentations took place at the level of atom which exhibited a significative negative charge.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The cleavage of the lactone ring take place at O 1 and then looses the CO after breaking the C 2 -C 3 bond, to give fragment A as indicated in the Schemes 2 and 3. When X = OH or NH 2 , fragment A (M-28) is the most abundant fragment as previously observed [11][12]14] and can lead to many other fragments as illustrated in the Schemes 2 and 3: Whether X = OH or NH 2 , the same fragmentation processes were practically obtained and good correlation with the electronic charges of atoms were observed. In this case, most of important fragmentations took place at the level of atom which exhibited a significative negative charge.…”
Section: Resultssupporting
confidence: 58%
“…The presence of odd molecular ions in mass spectra is indicative of the identity of the nitrogenated compounds. In previous papers [11][12], fragmentations of coumarins have been found to occur near the atoms bearing high negative charges. When X = OH or halogen, O 11 is known to be the site of the electronic beam impact, but when X is nitrogen moiety, the high negative charge of nitrogen suggests that N 13 could also be a site of the electronic beam impact, particulary in the case of dialkyl substituted nitrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been identified by their melting points and by their 1 H, 13 C and 17 O NMR spectra [3,5]. Mass spectra.…”
Section: Resultsmentioning
confidence: 99%
“…Their crystal structures have also been investigated [10][11][12]. Recently a new approach of analysis of fragmentation processes of coumarins in electron impact mass spectrometry has been described to give a good correlation with the electronic charges of their atoms [13][14][15]. It has been found that fragmentation processes in electron impact mass spectrometry (EIMS) takes place mainly at the level of atoms bearing high negative charge.…”
Section: Introductionmentioning
confidence: 99%